Guillelmus Durantis (1230/1237–1296) - Rafał Wojciechowski (Prawo)
In this article, the Author undertook the task of compiling a biography of Guillelmus Durantis, a bishop and legal scholar, and the characteristics of his work. The study reveals the author of Speculum iudiciale as a seasoned church official and a scholar in Roman and canon law. Because of his administrative and mediatorial talents, Durantis was often employed on matters requiring the Pope’s ongoing interventions. He organized and clarified the liturgy and presented the entire process now known as Roman-canonical process in a single work. Durantis’ findings closed many scientific and practical debates about the process for several centuries.